A Most Talked Exit of 2012: Warburg & Future Capital Deal - Joshi, Nisarg A; Desai, Jay M (IJRDO - Journal of Business Management, 2018)
With the global economic turmoil and the added uncertainty that has ushered in the Indian regulatory scenario since the beginning of the year 2012, it was only obvious for the total number of M&A transactions in the first half of 2012 slipping down as compared to 2010 and 2011. Having said that, it is rather surprising to note that the vast potential of the Indian market is still attracting a large number of foreign investors willing to offer attractive exit prices to the Indian promoters. This paper deals with one of the most-talked about exits of 2012, which was initiated in June 2012 when Mr. Kishore Biyani (promoter of Future Capital Holdings Limited (“FCH”)), after his long haul negotiations with several private equity firms finally squared down to US based private equity firm Warburg Pincus to sell Future Group’s stake in FCH, a non-core financial business of the Future Group. The Deal was launched on June 4, 2012 with the execution of definitive agreements between Cloverdell Investment Limited (“Cloverdell”), an entity belonging to Warburg Pincus, FCH and the promoters of FCH whereby Cloverdell agreed to acquire up to 55.36%1 of the issued and paid up equity share capital of FCH from the Sellers. With the closing of the Deal Cloverdell acquired 68.40% of the Diluted Voting Share Capital of FCH for a total consideration of approximately USD 136.5 million. This paper attempts to probe deeper into the Deal, a multi-million dollar transaction which provides Warburg the opportunity to test its fortune in the financial services sector in India and Future Group the opportunity to de-leverage its balance sheet and take its retail plans ahead, thereby proving to be in the best interests of both the parties. We seek to analyze the legal, regulatory, tax, financing and few other commercial dimensions of the Deal.